The Local Speech of Three Bistricas in Prekmurje - Zver, Nina (Slavia Centralis, 2023)
The local speech of three Bistricas – Gornja, Srednja and Dolnja – is classified as the southern variant (or dialect variant of Dólinsko) of the Prekmurje dialect of the Pannonian dialect group, but in some respects, it is closer to the speeches of Prlekija and Medžimurje dialects than to the neighbouring speeches of Dólinsko. The material-supported paper deals with those phonological, morphological, and verbal phenomena in the local speech of the three Bistricas, which are distinctive in relation to nearby local speeches and which linguists have too often generalized to the entire Prekmurje dialect. A list of uninhabited-area names of Gornja, Srednja and Dolnja Bistrica has also been added.
Keywords: dialectology, Prekmurje dialect, speeches of Dólinsko along the Mura, Pannonian dialect group, phonetics, morphology, words, uninhabitedarea names